If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = -3y Solving 42 = -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 42 + 3y = -3y + 3y Combine like terms: -3y + 3y = 0 42 + 3y = 0 Add '-42' to each side of the equation. 42 + -42 + 3y = 0 + -42 Combine like terms: 42 + -42 = 0 0 + 3y = 0 + -42 3y = 0 + -42 Combine like terms: 0 + -42 = -42 3y = -42 Divide each side by '3'. y = -14 Simplifying y = -14
| 0.4(x)+0.25(124-x)=38.44 | | -180=12f | | -13z=-65 | | 5n=8-9n | | 7x+5y+6z-4x+4z-8= | | 6-3(x-1)=7 | | (0.02-x)(2.5)=0.0125+x | | -12a=-39 | | 4x+10+x-30=180 | | Z+10=19 | | y/2.3=8 | | 1+7q=27 | | 1/2c=31/3 | | 3z-x=4z | | 2x^2+y^2+2yz+2z^2=0 | | 157=220-u | | ×/9=1/9 | | 2x=-0.5 | | 5+2x-x+x=10+x | | 5x+17=-23 | | Y-13=-8 | | r/5.8=11.6 | | 4-4x+3=5x-2 | | -3x^2-6x+2=0 | | 253=122-y | | 0.4(x)+0.25(132-x)=38.28 | | 1/2p-15=3/4p-3 | | x-5,2,3=2,1,3 | | 8x+4=16x+8 | | 12.1=2.2m | | -y+243=290 | | 5b+3b=16 |